Investigation and management of the unknown primary with metastatic neck disease: United Kingdom National Multidisciplinary Guidelines. (May 2016) - Mackenzie, K; Watson, M; Jankowska, P; Bhide, S; Simo, R
Abstract: This is the official guideline endorsed by the specialty associations involved in the care of head and neck cancer patients in the UK. It discusses the evidence base pertaining to the management of metastatic neck disease in the setting of an unknown primary and provides recommendations on the work up and management for this group of patients receiving cancer care. Recommendations: All patients presenting with confirmed cervical lymph node metastatic squamous cell carcinoma and no apparent primary site should undergo: ○ Positron emission tomography-computed tomography whole-body scan. (R) ○ Panendoscopy and directed biopsies. (R) ○ Bilateral tonsillectomy. (R) Tongue base mucosectomy can be offered if facilities and expertise exists. (G) Concomitant chemotherapy with radiation should be considered in patients with an unknown primary. (R) Concomitant chemotherapy with radiation should be offered to suitable patients in the post-operative setting, where indicated. (R) Neo-adjuvant chemotherapy can be used in gross 'unresectable' disease. (R) Patients should be followed up at least two months in the first two years and three to six months in the subsequent years. (G) Patients should be followed up to a minimum of five years with a prolonged follow up for selected patients. (G) Positron emission tomography–computed tomography scan at three to four months after treatment is a useful follow-up strategy for patients treated by chemoradiation therapy. (R)